Men's perspectives on HIV self-testing in sub-Saharan Africa: a systematic review and meta-synthesis - Mbuzeleni Hlongwa; Tivani Mashamba-Thompson; Sizwe Makhunga; Claudine Muraraneza; Khumbulani Hlongwana (BMC, 2020)
Abstract Background Despite the many HIV testing models implemented in Africa, the level of HIV testing uptake remains relatively poor, especially among men. The HIV self-testing (HIVST) model offers an additional approach for encouraging men to get tested. This study aimed to synthesise evidence on men's perspectives regarding HIVST in sub-Saharan Africa (SSA). Methods The databases searched included PubMed/MEDLINE, American Doctoral Dissertations via EBSCO host; Union Catalogue of Theses and Dissertations; SA ePublications via SABINET Online; World Cat Dissertations; Theses via OCLC; ERIC; CINAH; PsychInfo; Embase, Sociological Abstract, Scopus; and Google Scholar. The World Health Organization (WHO) and The Joint United Nations' Programme on HIV and AIDS (UNAIDS) websites were further searched. We only extracted qualitative information from the included studies, despite the research method used (qualitative or mixed methods). The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), as well as the Mixed Method Appraisal Tool (MMAT) version 2018, were used to determine the methodological quality of the included studies. NVivo version 11 was used for thematic analysis. Results A total of 21,184 articles were identified by the initial search criteria, but only 16 articles were included in the data extraction and quality assessment stage. The following key themes emerged: knowledge of HIVST; acceptability of HIVST; need for HIVST counselling; confidentiality of HIVST; convenience of HIVST; and accuracy of HIVST. The study shows that while HIVST provides men with an alternative, confidential and convenient testing model, the potential for psychological and physical harm remains a challenge. Conclusion The introduction of the HIVST strategy has the potential of improving men's uptake in HIV testing services, thereby contributing towards addressing the first cascade of the 90-90-90 strategy. While HIVST has a potential for addressing men's barriers to attending clinic settings, such as confidentiality and convenience, it barely addresses the HIVST counselling and accuracy concerns.